Evaluation of lymphocyte migration to induced paederus dermatitis: An experimental study in rats - Fereshteh Hosseini Valiki; Mohammad Mahdi Mohammadi; Abolghasem Ajami; Alireza Khalatbari; Farzad Motevalli Haghi (Wolters Kluwer Medknow Publications, 2019)
Background: Paederus dermatitis (PD) is a blistering disorder that is caused by a small insect of the genus Paederus, especially Paederus fuscipes. This study aimed to investigate the reaction of the adaptive immune system regarding the recruitment of CD3, CCR4, and CCR10 markers, which are specifically expressed on the surface of T lymphocytes. Materials and Methods: In this experimental study, 24 female rats were divided into two groups: the test and the negative control. In the test group, PD was induced by making insects in contact with shaved rat skin. Biopsies were obtained 24, 72, and 120 h after induction. In the negative control group, physiological saline was applied. Specimens were evaluated by immunohistochemical staining method. Antibodies against CD3, CCR4, and CCR10 were used. Distribution and staining intensities of CD3, CCR4, and CCR10 markers were estimated by the H-score index and findings were analyzed using the Kruskal-Wallis and Wilcoxon statistical tests. Results: Based on the results of immunohistochemistry, the expression of CD3, CCR4, and CCR10 in the test group at 24, 72, and 120 h compared to the control group showed significant increase (P = 0.0006, P = 0.001, and P < 0.0001), respectively. The peak of expression of all markers was at 72 h after exposure. Hematoxylin and eosin staining also confirmed the fact that the majority of the lymphocyte infiltration occurred at 72 h postexposure. Conclusion: The expression of CD3, CCR4, and CCR10 on cells present in PD lesions could indicate that T-lymphocytes are recruited to the site of inflammation by chemokine-chemokine receptor interactions and hence provide evidence for the response by the adaptive immune system following a PD.